Prenatal maternal stress in rats alters the epigenetic and transcriptomic landscape of the maternal-fetal interface across four generations - Stephanie E. King; Nicola A. Schatz; Olena Babenko; Yaroslav Ilnytskyy; Igor Kovalchuk; Gerlinde A. S. Metz (Communications Biology)
Abstract Prenatal maternal stress (PNMS) determines lifetime mental and physical health. Here, we show in rats that PNMS has consequences for placental function and fetal brain development across four generations (F0-F3). Using a systems biology approach, comprehensive DNA methylation (DNAm), miRNA, and mRNA profiling revealed a moderate impact of PNMS in the F1 generation, but drastic changes in F2 and F3 generations, suggesting compounding effects of PNMS with each successive generation. Both maternal and placental miRNA gene targets included de novo DNA methyltransferases, indicating robust PNMS-induced disruption in the complex epigenetic regulatory network between miRNAs and DNAm. Transgenerational programming mainly involved genes and biological pathways associated with neurological and psychiatric diseases which were linked to maternal-fetal crosstalk facilitated by the placenta. The highly correlated placenta-brain profiles support the use of placenta as a noninvasive biomarker resource to predict pathological changes in the neonatal brain. The transgenerational persistence of critical DNAm, miRNA and mRNA signatures may explain familial non-genetic disease risks.